DESAIN PEMBUATAN FILM DOKUMENTER KEHIDUPAN SANTRI - Rizkiani, Meti Agni (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
This paper describes how the life of santri and among its activities, include: study, self-study, cooking, friendly with nature, social interaction, and entrepreneurship. The life of this santri has its own charms, especially through ethnographic methods, this paper is studied by understanding the point of view of life from the point of view of the natives. With many advantages, the life of this santri becomes something interesting to be a documentary movie. Moreover, the object under study is a boarding school that still holds the values of tradition.